Government expenditure and poverty reduction in the proliferation of new administrative areas of Central Kalimantan, Indonesia - Andrie Elia; Yulianto Yulianto; Harin Tiawon; Sustiyah Sustiyah; Kusnida Indrajaya (Publisher of Widyagama University of Malang (UWG Press), 2020)
The proliferation of new region in Indonesia is one of the most challenging issues related to regional autonomy, financial management and poverty reduction. The purpose of this study was to analyze the relationship between government expenditure and poverty linked to the regional economic activity and labor absorption. The study used a quantitative research by means of time series data collected from the new proliferation areas in Central Kalimantan, including Pulang Pisau, Katingan, East Barito, Seruyan, Gunung Mas, Murung Raya, Sukamara, and Lamandau. The analysis method used the path analysis to estimate statistical parameters indicating relationship between variables. The research result shows that poverty significantly affects on government expenditure in the new eight regency in Central Kalimantan province. Poverty has also had an impact on government expenditure through the provision of employment and Gross Regional Domestic Product (GRDP). The local government is expected to manage more effectively regional finances that focus on community economic activities. The policy also opens investment opportunity to increase economic activity and create jobs based on the prominent regional product such as agriculture, plantation and mining sectors. Investment can increase employment and indirectly reduce poverty.JEL Classification H72; I38; J21